2009
DOI: 10.1016/j.cell.2009.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Nanog Is the Gateway to the Pluripotent Ground State

Abstract: SummaryPluripotency is generated naturally during mammalian development through formation of the epiblast, founder tissue of the embryo proper. Pluripotency can be recreated by somatic cell reprogramming. Here we present evidence that the homeodomain protein Nanog mediates acquisition of both embryonic and induced pluripotency. Production of pluripotent hybrids by cell fusion is promoted by and dependent on Nanog. In transcription factor-induced molecular reprogramming, Nanog is initially dispensable but becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

62
970
7
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 939 publications
(1,047 citation statements)
references
References 55 publications
(81 reference statements)
62
970
7
8
Order By: Relevance
“…For example, some reports proposed the expression of early differentiation markers as a characteristic of EpiSCs [3,17], whereas others reported the absence of these markers. Furthermore, some studies found that transcription factor overexpression was required for reversion of EpiSCs to an mESC-like state [5][6][7][8], whereas others showed reversion could be achieved by somewhat milder means just using stringent mESC culture conditions [4,9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, some reports proposed the expression of early differentiation markers as a characteristic of EpiSCs [3,17], whereas others reported the absence of these markers. Furthermore, some studies found that transcription factor overexpression was required for reversion of EpiSCs to an mESC-like state [5][6][7][8], whereas others showed reversion could be achieved by somewhat milder means just using stringent mESC culture conditions [4,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…They present conflicting views on their ability to revert to a state similar to that of mESCs (a mESClike state). Some studies suggest that transcription factor overexpression is required for the reversion of EpiSCs [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, transcriptome studies demonstrated that expression of OCT4, NANOG, and SOX2 was significantly lower in haGSC than in hESC, consistent with the notion that the promoter regions of OCT4 and NANOG were only partially demethylated in haGSC. As full demethylation of these promoters is an important criterion of complete pluripotency [30,31], this suggests that haGSC may only have acquired a partially reprogrammed state.…”
Section: Can In Vitro Culture Convert Germline Stem/progenitor Cells mentioning
confidence: 99%
“…11,12 Multipotentiality of stem cells has been strongly associated with expression of certain transcription factors such as Nanog, Oct3/4, Klf4, and Sox2. 13,14 It has been proposed that Nanog has a key role in maintaining embryonic stem cell pluripotency 15 ; however, stem cell pluripotency is also expressed in adult stem cells. 8 The ability of the progenitor cells to participate in scar formation, in particular insofar as maturation of fibroblasts into myofibroblasts, decreases with age.…”
mentioning
confidence: 99%